Analysis of Students' Creative Thinking Abilities in Mathematics Problems on Arithmetic Sequences and Series at SMA Negeri 1 Sedayu - Riska Natasi Br Ginting; Suhartati Suhartati; Naela Faza Fariha (Universitas Teknokrat Indonesia, 2026)
This study employs a descriptive qualitative approach, utilizing a case study method, to explore students' creative thinking abilities in depth when solving mathematical problems related to arithmetic sequences and series. The research subjects were 35 grade X students of SMA Negeri 1 Sedayu who were selected using a purposive sampling technique. Data were collected through essay tests that measure four indicators of creative thinking abilities: fluency, flexibility, originality, and elaboration, as well as semi-structured interviews and documentation of student work results. Data validity was tested through triangulation and observational persistence. The results showed that most students were classified as creative to very creative (77.1%). Fluency and flexibility aspects dominated, while originality and elaboration still varied among students. This study emphasizes the importance of providing open-ended questions and reflective learning to improve mathematical creative thinking abilities.